Pengembangan Media Promosi Kesehatan Sebagai Upaya Pencegahan HIV/AIDS pada Pekerja Sektor Swasta Formal - Sugiarto, Heri; Shaluhiyah, Zahroh; Widjanarko, Bagoes (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2010)
Now, the highest case number of HIV/AIDS was caused by sharing needle of injecting drug users. In the other hand, many drug users have a worker/employee back ground. The information about drug prevention is less to young workers. The goal of this research is health promotion media developing for formal private sector workers to prevent HIV/AIDS. This research is a qualitative research and using literature review to identify media information needs for workers and to be continued with health promotion media developing. The result of this research is showing that poster and film are appropriate media for workers. Based on this result could be conclude that poster and film could change respondent behaviour effectively for caring each other in drug misuse prevention related HIV/AIDS prevention, because this media has been developed suitable with workers characteristic and need. For factory sectors are suggested to put this media at their strategic place and for the next research is suggested doing with intervention and evaluation phase.